Association of complex ferrumcyanide anions with pinacyanol cation in aqueous solution - Larin, Vasil'; Shapovalov, Serghiy (Publishing House of Lviv Polytechnic National University, 2012)
The possibility of associates formation between complex ferrumcyanide anions [Fe(CN)6]3–, [Fe(CN)6]4– and cationic polymethine dye pinacyanol in aqueous solution has been investigated. Energetic characteristics and the structures of associates were determined and the influence of ionic surfactants on the associates has been considered. Встановлена можливість утворення асоціатів між ферумціанідними металокомплексними аніонами [Fe(CN)6]4–, [Fe(CN)6]3– і катіонним поліметиновим барвником пінаціанолом у водному розчині. Визначено енергетичні характеристики і будову асоціатів, розглянуто вплив на асоціати йонних ПАР.
Асоціація комплексних ферумціанідних аніонів з катіоном пінаціанола у водному розчині
Keywords: association; aqueous solution; complex ferrumcyanide anions; surfactants; absorption spectra; pinacyanol; асоціація; водний розчин; ферумціанідний металокомплекс; ПАР; спектри поглинання; пінаціанол